Prophet Ibrahim (as), the Search for God and a Transformative Pedagogy Perspective - Nurul Hidayat; Ngainun Naim (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
Transformative pedagogy is the latest trend in educational studies. This is inseparable from several concepts, one of which is the study of human nature. So far, pedagogic understanding emphasizes the ability to manage student learning rather than understanding human nature. On the other hand, studies on Prophet Ibrahim’s (as) search for God in the Quran is an important subject to investigate from the perspective of transformative pedagogy since it is related to human nature. This study is included in the literature research. The method used was tafsir maudlu’iy namely by gathering verses of the Quran that have the same theme and analyzing them with the rules of interpretation. The results of this study show that Prophet Ibrahim (as) is not passive, but has energy or magmatic. This energy shows Prophet Ibrahim (as) as autonomous “I” that is in the process of becoming. This process is a search for God. This process subsequently develops from ‘ilm al-yaqin to ‘ayn al-yaqin. This study has a contribution in developing the theory proposed by H.A.R Tilaar into Transcendental Transformative Pedagogy. Keywords: Transformative Pedagogy, Educational Studies, Millenial Generation